2015
DOI: 10.1121/2.0000041
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on the nonlinear oscillations of contrast enhancing microbubbles

Abstract: Micron-sized, gas encapsulated bubbles are used as ultrasound contrast agents to improve diagnostic image quality. These microbubbles, which are vascular agents, undergo linear and non-linear oscillations when excited. It is the non-linear response of microbubbles that facilitates the ability to distinguish between signals from the tissue -mostly linear-, and signals from the bubbles, which represents vasculature. This opens up numerous clinical applications such as echocardiography, focal lesion identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the stability of Definity ® may reduce once the phase transition has been reached. These results should be considered if Definity ® is used for hyperthermia or UCA-enhanced heating studies (Guiot 2004; Guiot 2006; Meral 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the stability of Definity ® may reduce once the phase transition has been reached. These results should be considered if Definity ® is used for hyperthermia or UCA-enhanced heating studies (Guiot 2004; Guiot 2006; Meral 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mulvana et al (2011) performed high-speed imaging of SonoVue ® exposed to ultrasound, and observed stronger radial excursion, shell fragmentation, and jet formation at body temperature than at room temperature. Meral et al (2014) investigated the impact of temperature on the stable cavitation activity of a lipid-shelled UCA. Increasing the temperature from 25 °C to 40 °C was reported to increase subharmonic scattering relative to harmonic scattering by 10 dB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation